Interdisciplinarity and Undergraduate Psychology Education. (June 2013) - Goodwin-Smith, Ian; Pearson, Elissa; Ranzijn, Rob; Campbell, Alan; Lushington, Kurt
This work identifies the human service sector as an important and growing destination for psychology graduates. It further identifies a number of key themes which flow from that observation and which are important to configuring psychology education in a way which takes account of emerging trends. The major theme identified in the research is the importance of breadth. The theme of the importance of breadth takes two related and repeated forms. The first is that graduates need to be thinkers rather than doers. The second is that employers in the human services stress the need for broad-based thinking and analytical skills to reflect social and contextual awareness of therapeutic situations and human service programmes and interventions. Stakeholders broadly commented that graduates seeking employment in the human service sector need upskilling in terms of a contextual awareness of the 'real world'. One idea which emerged in this research is that real-world multidisciplinarity is best underpinned by an interdisciplinary approach to teaching and learning.